2012
DOI: 10.12968/bjon.2012.21.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia part 1: pathology, presentation and prevention

Abstract: Pneumonia is a significant cause of morbidity and mortality and can affect all age groups although it is the very young and the very old who are most at risk. Pneumonia can be caused by many different organisms and can present as a primary condition or as a complication of other diseases or acute health problems. This article will give an overview of the disease, its symptoms and treatment and will focus primarily on community-acquired pneumonia. Two further articles will look at specific causative organisms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
1
8
0
1
Order By: Relevance
“…Admission for LRI was higher than for URI, consistent with other studies conducted in hospital setting, qualifying LRI as the second cause of morbidity and the fourth leading cause of mortality in all age groups in 2013 with a high burden related to pneumonia [ 19 21 ]. However, URI has long been regarded as the most frequent RI in community [ 22 ].…”
Section: Discussionsupporting
confidence: 85%
“…Admission for LRI was higher than for URI, consistent with other studies conducted in hospital setting, qualifying LRI as the second cause of morbidity and the fourth leading cause of mortality in all age groups in 2013 with a high burden related to pneumonia [ 19 21 ]. However, URI has long been regarded as the most frequent RI in community [ 22 ].…”
Section: Discussionsupporting
confidence: 85%
“…It is well-known that inflammation can damage the normal lung structure and cause exudation of inflammatory products (Driver, 2012). Through the histopathological observation, we found that magnoflorine inhibited the infiltration of inflammatory cells and restrained the alveolar structural damage.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that more than 150 million cases occur annually among children under 5 years old, leading to approximately 2 million deaths each year ( 1 ). Pneumonia is a lower respiratory tract disease characterized by an intense inflammatory response, which results in increased lung edema, loss of respiratory area, and can lead to respiratory impairment and death ( 2 4 ). It can be caused by several pathogens, such as virus, fungi, and bacteria.…”
Section: Introductionmentioning
confidence: 99%